No difference in mid-term outcome after superior vs. anteroinferior plate position for displaced midshaft clavicle fractures - Philip-Christian Nolte (Nature Portfolio, 2021)
Abstract To compare outcomes, complications, revisions, and rates of implant removal of superior compared to anteroinferior plating in displaced midshaft clavicle fractures at mid-term follow-up. We retrospectively reviewed 79 patients who underwent operative treatment for displaced midshaft clavicle fractures (Group A: 28 patients with superior plating; Group B: 51 patients with anteroinferior plating) that were at least 2 years postoperatively. Adjusted Constant Score (aCS), Visual Analog Scale (VAS), and Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) score were compared. Bone union, implant removal, complications and revision surgeries were assessed. Group A had a significantly higher aCS compared to group B (90, IQR: 85.0–91.0 vs. 91, IQR: 90.0–93.0; P = 0.037). No significant differences between groups were seen in VAS (P = 0.283) and QuickDASH (P = 0.384). Bone union was achieved in 76 patients (96.2%) with no significant differences between groups (Group A: 96.4% vs. Group B: 96.1%; P > 0.999). There were no significant differences in implant removal rates (Group A: 60.7% vs. Group B: 66.7%; P = 0.630), complications (Group A: 46.4% vs. Group B: 31.4%; P = 0.226) and revisions (Group A: 25% vs. Group B: 9.8%; P = 0.102). Superior and anteroinferior plating result in high bone union rates and good clinical outcomes with similar rates of plate removal.